Rekomendasi Wisata Pantai di Sekitar Malang berbasis Android dengan Group Decision Support System dan Location Based Service - Mujahid Bariz Hilmi; Ratih Kartika Dewi; Muhammad Aminul Akbar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Malang has the potential for beach tourism which can be one of the factors that can improve its own development and power. Previously, there was a recommendation system in determining beach tourism destinations but only limited to the use of 1 user. Therefore, a recommendation application development using the Group Decision Support System (GDSS) approach can be developed which can be used to help tourists who come in groups to determine their tourist destinations. The TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) method is implemented to determine alternative tourism destination choices and Borda is used for group voting to determine group recommendations. Application development is done on an android basis using Location Based Service (LBS) so that it can adjust to the user's location to determine recommendations. This study discusses the analysis of user needs, design of system, design of algorithm, implementation of the system, test and evaluation of system. From the blackbox test we get a valid result where all functions can work well. In algorithm testing, the recommendations displayed by the system are the same as for manual calculations. Usability testing produces an average value of 75 of 5 respondents who were measured using the SUS method, so it's known that the system that built can be properly used by users.